Systemic inflammatory response syndrome in ureteroscopy: frequency, risk factors, and implications for prevention - Venegas-Yañez, César E.; Anceno, Alec; Fernandez-Noyola, Gerardo; Alvarado-Bahena, Pedro A.; Cervantes-Zorrilla, Ricardo; Silva-Mendoza, César A.; Miranda-Blasnich, Héctor A.; Martínez, Marco A. Ascencio; Magdaleno-Rodríguez, Daniel R.; Lerma-Landeros, Jesús E.; Vázquez-González, Juan C.; Pérez-Silva, Luis A.; et al. (International Surgery Journal, 2025)
Background: Systemic inflammatory response syndrome (SIRS) is a preventable cause of morbidity and mortality in patients undergoing ureteroscopy for urinary stone treatment. Multiple factors, including diabetes, hypertension, positive urine cultures, prophylactic antibiotics, and procedure duration, may influence SIRS risk, but their individual roles remain unclear. Methods: A descriptive, retrospective, and prospective cross-sectional study was conducted at Hospital General Dr. Manuel Gea González from January 2021 to December 2024. Inclusion criteria encompassed patients aged ≥18 years undergoing ureteroscopy. Data were collected on comorbidities, stone characteristics, procedural details, and outcomes. Statistical analyses were performed using logistic regression to identify risk factors. Ethical approval was obtained. Results: Among 351 patients, 60 (17.09%) developed SIRS. Factors associated with higher SIRS rates included flexible ureteroscopy (73.33%), ureteral access sheath use (50%), postoperative stents (60%), and preoperative positive urine cultures (33.33%). Patients with harder stones (≥1175 HU) experienced longer operative times (≥75 minutes). Conclusions: Flexible ureteroscopy, ureteral access sheaths, postoperative stents, and positive urine cultures are significant risk factors for SIRS.